Economic Intuition to Social Capital: Household Evidence from Jimma Zone, South-West Ethiopia - Haile, Minyahil Alemu; Whakeshum, Sisay Tola (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
The notion of social capital is noble in social science literatures and recently getting noteworthy attention in economics. Its economic relevance has also been well documentedin empirical studies. In this paper, we established relationshipsbetween the stock of household social capital and annual net income following approach for binary logit. Besides, we examined the relative economic importance of general viz special stocks of social capital. Statistical requirements with logistic regression were all tested robust. Consequently, the effectof social capital stock on household economy has found substantial. Of the two distinct forms, the special facet of social capital was found better and significant contributor to householdeconomy. However,the general aspect was suggested insignificantasit was not meaningfully interpreted in the household economic network.Thus, a wise household need to appropriate the general to special social capital establishment, since every additional stock of the later could be meant to considerablyhelp own welfare.